Effects of resistance training on depression and cardiovascular disease risk in black men: Protocol for a randomized controlled trial. (October 2019) - Busch, Andrew M.; Louie, Mark E.; SantaBarbara, Nicholas J.; Ajayi, Alex A.; Gleason, Neil; Dunsiger, Shira I.; Carey, Michael P.; Ciccolo, Joseph T.
Abstract: Background: Depression is severely undertreated in Black men. This is primarily because Black men are less likely to seek traditional psychiatric treatment, have less access and more barriers to treatment, and perceive more stigma associated with treatment. Depression contributes to cardiovascular disease (CVD), and Black men have the highest rate of mortality from CVD. Resistance training (RT) can have beneficial effects on both depression and CVD. This study will be the first randomized controlled trial to test the effects of RT on depression and cardiovascular health in a sample of depressed Black men. Method: Fifty Black men with clinically significant symptoms of depression will be randomized to either (a) a 12-week RT or (b) an attention control group. Behavioral Activation techniques will be used to support adherence to home-based RT goals. Both groups will meet on-site twice/week during the 12-week program, and follow-up assessments will occur at the end-of-treatment and 3 months post-treatment. Qualitative interviews will be conducted after the 3-month follow-up. The objectives of this study are (1) to assess the feasibility and acceptability of recruitment, retention, and intervention procedures, (2) to obtain preliminary evidence of efficacy, and (3) to explore potential mediators of the effects of RT on depression. Discussion: This study will advance the field of minority men's health by producing new data on the effects of RT for depression, the potential mechanisms of action that may support its use, and its effects on markers of CVD risk in Black men. Trial registration: ClinicalTrials.gov (NCT03107039); Highlights: Black men experience high rates of heart disease morbidity and mortality. Depression contributes to heart disease and is undertreated in Black men. Current psychiatric depression treatments are unacceptable to many Black men. Weight lifting may improve both depression and heart health. This study will test the effect of weight-lifting in depressed black men.